The dialogic presentation as a more compassionate approach - Laura Dyer (Journal of Learning Development in Higher Education)
Presentations are a common means of communication worldwide with learners expected to carry out presentations as a means to disseminate academic knowledge (Tsang, 2020).  Yet despite the issues that presentations induce in terms of stress (Merz et al., 2019), concerns over inclusivity (Mann and Clift, 2021), lack of presentation experience (Bankowski, 2010) and questions over transferable skills (Byrne, 2020), the traditional monologic presentation remains at the forefront of assessing through speaking. This lightning talk called for change and showed how the traditional monologic presentation is no longer relevant to today’s teaching and learning in higher education.